The effect of 12 weeks brain jogging based learning models to improve gross motor skill: object control skill in elementary school - Willy Ihsan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The motor skills of children can be used to determine whether or not the child's growth and development is impaired. The aim of the study to know the effect of brain jogging based learning model improving the object control skills of elementary school students. This study was conducted using an experimental method with two groups, namely control and intervention. In comparison to traditional learning models (direct instruction), the brain jogging based learning model. This study's sample consisted of the total number of students in the subject is 60. Classes 4A and 4B have similar characteristics (age, average height/weight, sports learning material, duration, and time of sports learning implementation).Data processing was conducted using SPSS IBM 26. The mean difference in the post-test result between the control and experimental group was based on the significance of the SPSS output(p<0.05). Based on the output in the Independent sample t test it is known that the value of two hand striking a stationary is 0.039 < 0.05; forehand strike of 0.009 < 0.05; one hand stationary dribble of 0.039 < 0.05; d two hand catch of 0.000 < 0.05; kick a stationary ball of 0.004 < 0.05; overhand throw of 0.002 < 0.05; underhand roll of 0.020 < 0.05. There is a significant influence statistical analysis on two hand striking stationary, forehand strike, one hand stationary dribble, two hand catch, kick a stationary ball, overhand throw, and underhand roll ability for elementary school with the Brain jogging based learning model can be one solution to improve the performance of object control skill.